Design of a polyurethane underwater sound absorber based on the BP neural network and genetic algorithm - Wang, Feng; Chang, Shan; Xie, Jie (Frontiers in Physics, 2022)
A coordinate transformation theory for acoustic cloak design based on pentamode material was proposed by Norris in 2008. This theory avoids the problem of infinite density at the inner boundary of inertial cloak, but the structural design of pentamode material was difficult to achieve. In order to solve this manufacturing problem, a design scheme of a low scattering cloak with only a few layers of polyurethane materials is proposed in this paper. Firstly, material parameter distribution of the acoustic cloak was obtained based on the coordinate transformation theory. On this basis, material parameter distribution in the two-dimensional annular acoustic cloak was derived by using linear mapping. Through the simulation comparison between uncovered acoustic cloak and covered acoustic cloak, the equivalent scattering characteristics of obstacles covered with acoustic cloak was significantly reduced, which shows that anisotropic concealed materials have obvious advantages in acoustic control. When the thickness was given and the frequency was fixed, the sound pressure field of the cloak is simulated under the condition of uniform stratification. With the increase of the number of layers, the stealth effect is better, and the complexity of the preparation of metamaterials is increased. In order to obtain the cloak structure with simple structure and good stealth performance, BP neural network genetic algorithm and sound field finite element modeling were using. Taking the minimum scattering area as the optimization goal, and trying to find the design scheme of low scattering cloak with only a few layers of polyurethane materials. The optimization results show that when the target frequency is 2KHz and the number of cloak layers is 5, the optimized scattering area is 73% less than that of the uniform layered structure. This shows that anisotropic stealth materials have obvious advantages in sound control. This study can guide the cell configuration design of polyurethane materials in different positions, and greatly simplify the complexity of the manufacturing process of stealth materials.